Decor-Räume in pompejanischen Stadthäusern Ausstattungsstrategien und Rezeptionsformen - Haug, Annette (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2020)
The book examines the decorative principles taking effect in the houses of Pompeii between the end of the 2nd century BCE and the early Imperial period. For the first time, individual decor phenomena are not only considered in isolation, but also in terms of their spatial and social relationship.